Biomimic Nanodrugs Overcome Tumor Immunosuppressive Microenvironment to Enhance Cuproptosis/Chemodynamic‐Induced Cancer Immunotherapy - Hangyi Wu; Xiaoyu Lu; Yuhan Hu; J. Baatarbolat; Zhihao Zhang; Yiping Liang; Youwen Zhang; Ye Liu; Huixia Lv; Xin Jin (Advanced Science)
Abstract Elesclomol (ES) as an efficient Cu ionophore can specifically transport Cu into mitochondria and disrupt intracellular Cu homeostasis. Extra intracellular Cu induces cuproptosis and chemodynamic therapy (CDT), which further cascades immunogenic cell death (ICD) and activates antitumor immune responses. However, the tumor immunosuppressive microenvironment (TIM) attenuates the efficiency of the immune response. Herein, a biomimic nanodrug (ECNM) is fabricated, of which ES, Cu2+ and NLG919 (an IDO1 inhibitor) are integrated via a self‐assembly process and subsequently coated with 4T1 cell membrane. ECNM can overcome the typical drawbacks of ES, ameliorating the stability and half‐life of ES by membrane‐coating and enhancing its tumor accumulation and internalization via homotypic targeting. It is worth mentioning that, the addition of NLG919 is also beneficial to the system circulation stability of ES and reduces the non‐specific ES release. After internalization, ECNM dissociates via the glutathione‐responsive process and exhibits comprehensive antitumor capabilities, including cuproptosis, CDT and TIM reversing, thereby eliciting ICD and optimizing the antitumor immune response. Furthermore, ECNM not only accelerates tumor regression but also gains a strong abscopal effect and displays the potential of tumor vaccination. Overall, ECNM can activate antitumor immunity via cuproptosis and CDT, together with TIM reversing, for cancer treatment.